2007
DOI: 10.20867/thm.14.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Silence: A Survey on Employees Working in a Chain Hotel

Abstract: The purpose of this study is to research reasons of silence in organizations, its effects, results and applications which can minimize or remove silence by explaining silence concept. Other purpose is to measure attitudes of managers and employees towards silence climate in organizations. In this sense, Questionnaires were applied a chain hotel company which has 3 hotels in Antalya, 278 questionnaires were delivered and 135 of them were taken. Questionnaire data was analyzed, and according to the results, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Contrary to these findings, Okeke-James, Igbokwe, Anyanwu and Obineme (2020) who conducted research among school teachers and tried to find the relation between gender influence on organizational silence, found no significant relationship between male teachers and female teachers regarding the silence in both open and closed school climates. Ehtiyar and Yanardağ (2008) who conducted research in a chain hotel, found that the silence levels of men and women were almost the same. Likewise, Özdemir and Sarıoğlu (2013) conducted research in the public and private sectors and concluded that organizational silence does not differ according to gender.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Contrary to these findings, Okeke-James, Igbokwe, Anyanwu and Obineme (2020) who conducted research among school teachers and tried to find the relation between gender influence on organizational silence, found no significant relationship between male teachers and female teachers regarding the silence in both open and closed school climates. Ehtiyar and Yanardağ (2008) who conducted research in a chain hotel, found that the silence levels of men and women were almost the same. Likewise, Özdemir and Sarıoğlu (2013) conducted research in the public and private sectors and concluded that organizational silence does not differ according to gender.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Çalışanların bilinçli ve kasıtlı olarak gerçekleştirdikleri sessizlik davranışları, etkili örgütsel öğrenmeye, çevreye uyum sağlama gücüne ve güvenirliğe ciddi zararlar verebilmektedir (Acaray, 2014:142). Bunun yanında alan yazında örgütsel sessizliğin; kontrol duygusu eksikliğine bağlı olarak fizyolojik veya psikolojik yılgınlık ve motivasyon kaybı (Ehtiyar ve Yanardağ, 2008:58;Deviren ve Okçu, 2020:915), kin ve nefret duygusu yaşama, yaratıcılığın, heyecanın azalması ve verimliliğin düşmesi (Akay, 2017:27), örgütsel güvenin azalması (Fard ve Karimi, 2015, Karakavuz, 2021, örgütsel performansın azalması (Şehitoğlu, 2010), işten ayrılma niyetinin oluşması (Alparslan, 2010;Öge, 2021), yaşam doyumunun azalması (Akbaş, Gemlik ve Çatar, 2020), örgütsel bağlılığın ve iş doyumunun azalması (İşlek ve Bakioğlu, 2023, Wang et all, 2022, Rayan et all, 2020, örgütsel özdeşleşmenin azalması (Atmaca, 2021), örgütsel sinizmin oluşması (Nartgün ve Kartal, 2013, Düzgün, 2022, yabancılaşma (Ehtiyar ve Yanardağ, 2008:59, Çiftçi ve Öneren, 2017 vb. olumsuz sonuçlara yol açtığını ortaya koyan birçok çalışmanın olduğu görülmektedir.…”
Section: Teorik çErçeveunclassified
“…It is stated that although favouritism continues to be an important phenomenon in hospitality sector, there is little empirical work regarding the consequences of favouritism in hotel context (Arici, et al, 2020). Besides that, while employee silence is significantly present in organisations, it is observed that there are few empirical studies in the literature to define, analyse and deal with employee silence (Ehtiyar and Yanardağ, 2008).…”
Section: Introductionmentioning
confidence: 99%